Resveratrol attenuates visfatin and vaspin genes expression in adipose tissue of rats with type 2 diabetes - Soheila Asadi; Mohammad Taghi Goodarzi; Massoud Saidijam; Jamshid Karimi; Reza Yadgar Azari; Azam Rezaei Farimani; Iraj Salehi (Iranian Journal of Basic Medical Sciences, 2015)
Objective(s): Visfatin and vaspin are secreted by adipose tissue and play key roles in glucose homeostasis and subsequently are potential targets for diabetes treatment. Resveratrol (RVS) corrects insulin secretion and improves insulin sensitivity. We investigated the RVS effects on serum antioxidants, insulin and glucose levels, also visfatin and vaspin genes expression in adipose tissue of streptozotocin-nicotinamide (STZ-NA) induced type 2 diabetic rats. Materials and Methods: Diabetes was induced in Wistar rats (n=32) using STZ (60 mg/kg body weight) and NA (120 mg/kg body weight); rats were divided into 4 groups (n=8). Eight untreated normal rats were used as control group; four diabetic rat groups (2–5) were treated with 0, 1, 5 and 10 mg /kg body weight of RVS, respectively for 30 days. After treatment blood and adipose tissue were prepared from all animals. Serum glucose, insulin, HOMA index, total antioxidant capacity (TAC), and malondialdehyde (MDA) were measured. Visfatin and vaspin genes expression in adipose tissue were evaluated using real-time PCR. Results: RVS reduced blood glucose significantly and increased insulin level, resulting in insulin sensitivity improvement. Furthermore RVS increased weight and TAC, while reducing serum MDA in the diabetic groups. Visfatin gene expression increased in the diabetic group, and RVS treatment reduced it. Vaspin gene expression was reduced in RVS receiving diabetic groups. Conclusion: The results indicated that RVS has potential hypoglycemic effect, probably by increasing insulin level and changing gene expression of visfatin and vaspin. Moreover RVS showed antioxidant effects through reduction in peroxidiation products and augmented antioxidant capacity.